Visualisasi Kubur Sekunder Komunal di Pulau Samosir (Pendekatan Komunikasi Visual dalam Usaha Meningkatkan Kunjungan Wisata) - Defri Elias Simatupang (Balai Arkeologi Sumatera Utara, 2010)
AbstractDiscussion on the visualization of secondary communal graves on Samosir intended to study the problems related to the captured messages by the public based on visual signs that are used when looking at a tourism promotion. Messages that are captured visually by the communicants (receiver of the messages) apparently can differ from the initial messages from communicator (sender of the messages). Through visual communication approaches that deliver is expected the messages can be accepted by the public in order to increase the tourist visits.